DETERMINATION OF PARAMETERS OF A SMALL POWER PLANT ON A RIVER WITH AN ENERGY-ABSORBING SURFACE IN THE FORM OF A SINUSOIDAL HELICOID - Kapitanchuk Kostіantyn; Andriyishyn Мuhаilo (Science-based technologies, 2025)
By using the hydropower potential of small rivers, Ukraine can achieve significant savings in fuel and energy resources. The development of small hydropower will contribute to the decentralization of the overall energy system: it will solve a number of problems in the energy supply of remote and hard-to-reach rural areas and the management of giant energy systems; a whole range of problems in the economic, environmental and social spheres of life and management in rural areas, including in district centers, will be solved. The total hydropower potential of small rivers in Ukraine is about 12.5 billion kWh, which is about 28% of the total hydropower potential of all its rivers. Mini-hydroelectric power plants and micro-hydroelectric power plants can become a powerful basis for energy supply for all regions of Western Ukraine, and for some areas of Transcarpathian and Chernivtsi regions - a source of complete autonomous energy supply. In 2004, scientists from the National Aviation University presented the development of a flexible energy-absorbing surface for a wave power plant, which, according to the principle of wave energy conversion, was fundamentally different from existing ones and was able to generate electricity during any extraordinary disturbances of the sea surface. A sinusoidal helicoid, which is created from a flat ribbon when it rotates relative to its axis (shaft) by surface waves on the seas, is able to create a torque and transmit power to an electricity generator. If you artificially create a sinusoidal helicoid for the real flow speed in a river, you can get the same effect, and the geometry of the helicoid will be optimal - created by nature. The surface of the energy-absorbing element of a micro-hydroelectric power plant in the process of its movement under the action of the energy of the water flow is calculated for one mode of the highest load of its main nodes. To make a decision on the manufacture of individual components of the station, after determining the required capacity from the customer and the energy potential of the river directly at the site of the station (flow velocity, depth, length restrictions, etc.), it is necessary to carry out calculations according to the methodology for determining energy indicators and geometric dimensions of micro-hydroelectric power plants.